Adams Square and Scollay Square, December 3, 1962 - Boston Traveler (Tufts Archival Research Center, 2005)
Elevated view looking towards Scollay Square from the Faneuil Hall cupola. In the foreground is Adams Square at Washington Street, Brattle Street runs up toward New Suffolk County Courthouse. On the right is Elm and Friend Streets which run off of Union Street which runs into Haymarket Square. 6 1/8 x 8 1/2 overall 7 1/8 x 9 1/16 Photographs